The elastic properties of hexagonal auxetics under pressure. Issue 7 (18th May 2016) - Goldstein, Robert V.; Gorodtsov, Valentin A.; Lisovenko, Dmitry S.
Abstract : Elastic properties of the hexagonal crystals under pressure were analyzed. Seven crystals with negative Poisson's ratio (auxetics) were revealed at zero pressure. These are crystals of MoS2, Zn, Be, BeCu (alloy with 2.4 at.% Cu), TiB2, C7 H12, and MnAs. Analytical expressions of extreme values of Poisson's ratio and Young's modulus were obtained. For these materials, the variability of Poisson's ratio and Young's modulus was analyzed at pressure change. It was shown that all seven hexagonal auxetics may become completely auxetic under certain pressure values. The variability of the elastic properties of graphite and SiC, being non‐auxetics at zero pressure, was considered. These crystals become partially auxetic at negative pressure (−15 GPa for graphite and −56 GPa for silicon carbide) and completely auxetic at −114 and −122 GPa, respectively. The surface of auxeticity ν ( θ, ψ ; p ) = 0 for hexagonal auxetic MoS2 .